2009
DOI: 10.1103/physrevc.79.034606
|View full text |Cite
|
Sign up to set email alerts
|

Isospin dependence of projectile-like fragment production at intermediate energies

Abstract: Ni are compared and the isospin dependence of the projectile fragmentation is studied. It is found that the isospin dependence decreases and disappears in the central collisions. The shapes of the fragment isotopic and isotonic cross section distributions are found to be very similar for symmetric projectile nuclei. The shapes of the fragment isotopic and isotonic distributions of different asymmetric projectiles produced in peripheral reactions are found very similar. The similarity of the distributions are r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…T of a neutron-rich reaction system is higher than that of the neutron-proton symmetric reaction systems when similar measurements are made, i.e., T ( 136 Xe) > T ( 124 Xe), and T ( 124 Sn) > T ( 112 Sn). This is a similar phenomenon as the isospin dependence of the fragment yields measured in reactions of neutron-proton symmetric and neutron-rich reactions [49]. The isotopic temperature (T HeLi ) was also found to increase when the [47], (e) 140A MeV 48 Ca + 9 Be/ 181 Ta [48], and (f) 140A MeV 64 Ni + 9 Be/ 181 Ta [48].…”
Section: Isobaric Yield Ratio Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…T of a neutron-rich reaction system is higher than that of the neutron-proton symmetric reaction systems when similar measurements are made, i.e., T ( 136 Xe) > T ( 124 Xe), and T ( 124 Sn) > T ( 112 Sn). This is a similar phenomenon as the isospin dependence of the fragment yields measured in reactions of neutron-proton symmetric and neutron-rich reactions [49]. The isotopic temperature (T HeLi ) was also found to increase when the [47], (e) 140A MeV 48 Ca + 9 Be/ 181 Ta [48], and (f) 140A MeV 64 Ni + 9 Be/ 181 Ta [48].…”
Section: Isobaric Yield Ratio Methodssupporting
confidence: 73%
“…The SAA model can well reproduce the yield of fragments [49] and was used to study the isospin phenomena in HICs [55][56][57][58]. In brief, in the SAA model, the prefragment is calculated after the numbers of abraded protons and neutrons are known, which are determined by the nuclear-density distribution in the overlapping zone of projectile and target, and the nucleon-nucleon reaction cross section.…”
Section: Isobaric Yield Ratio Methodsmentioning
confidence: 99%
“…Using the SAA model [15][16][17][18][19][20], the fragments produced in the 80 A MeV odd calcium isotopes 36−52 Ca+ 12 C projectile fragmentation are calculated. In the calculation, the free space nucleus-nucleus cross sections [21] and the Fermi-type density distributions [7,22] are adopted:…”
Section: The Calculationsmentioning
confidence: 99%
“…These effort to combine the experimental observable to δ np of the neutron-rich nucleus is helpful to study the neutron distribution of neutron-rich nucleus. It is found that isospin effect in the projectile fragmentation of asymmetric neutron-rich matter will influence the fragment isotopic cross section distributions [15][16][17]. In this article, the correlation between δ np of the calcium isotopes and the isospin effect in the fragment isotopic cross section distributions of their projectile fragmentation will be studied.…”
Section: Introductionmentioning
confidence: 99%
“…The SAA model is a two-stage model to predict fragment yield in HICs [22,23]. By distinguishing the neutron and proton densities, the modified SAA model can well reproduce isotopic (isotonic) yields in asymmetric reactions systems [24][25][26], and can be used to investigate phenomena originated from neutron-proton asymmetry or neutron skins [26][27][28][29][30][31][32][33]. In the SAA model, the first stage describes the collision in which the nuclei are assumed to be infinitesimal parallel tubes orienting along the beam direction.…”
mentioning
confidence: 99%